Evaluation of shot peening on the fatigue strength of anodized Ti-6Al-4V alloy - Costa,Midori Yoshikawa Pitanga (2006)
The increasingly design requirements for modern engineering applications resulted in the development of new materials with improved mechanical properties. Low density, combined with excellent weight/strength ratio as well as corrosion resistance, make the titanium attractive for application in landing gears. Fatigue control is a fundamental parameter to be considered in the development of mechanical components. The aim of this research is to analyze the fatigue behavior of anodized Ti-6Al-4V alloy and the influence of shot peening pre treatment on the experimental data. Axial fatigue tests (R = 0.1) were performed, and a significant reduction in the fatigue strength of anodized Ti-6Al-4V was observed. The shot peening superficial treatment, which objective is to create a compressive residual stress field in the surface layers, showed efficiency to increase the fatigue life of anodized material. Experimental data were represented by S-N curves. Scanning electron microscopy technique (SEM) was used to observe crack origin sites.